Heritage. Discussion Club of the UAR IRO - Tkacheva, Marina (project baikal, 2021)
The problems of heritage were considered in the context of preservation of the historical look of the city. The participants of the discussion highlighted the significance of the restoration of cultural heritage and compared the restoration principles in different countries. They discussed the issues related to restoration education, methods of involving students and active youth in the promotion of the image of the city and the region.